Burnout Syndrome in Moroccan Training Resident: Impact on Quality of Life - Jihane BELAYACHI; Ilham RKAIN; Hanane RKAIN; Naoufel MADANI; Fatiha AMLAIKY; Aicha ZEKRAOUI; Tarek DENDANE; Khalid ABIDI; Amine Ali ZEGGWAGH; Redouane ABOUQAL (Tehran University of Medical Sciences, 2016)
No Abstract.